DESKRIPTIF LITERATUR REVIEW DISKRIMINASI PENYANDANG DISABILITAS DALAM DUNIA KERJA - Zira Aura Sekarini; Hastin Trustisari (JURNAL ILMIAH NUSANTARA, 2024)
Background: Getting a decent job is the right of every individual, regardless of social status. In Indonesia, this is regulated in Article 27 Paragraph 2 of the 1945 Constitution which states that "every citizen has the right to work and earn a decent livelihood", as well as people with disabilities. Objective: This review literature aims to provide in-depth insight into the discrimination faced by people with disabilities in the world of work, as well as provide recommendations to improve current conditions. Method: This study uses a descriptive literature review method, which is to search for literature from journals through Google Scholar. Results: The results of the analysis of several articles that have been explained above show that discrimination against people with disabilities in the world of work is still widely felt by people with disabilities. Conclusion and Suggestion: Discrimination is still felt by people with disabilities, both in the work environment and the social environment. This has a quite serious impact on people with disabilities, both physically and emotionally. Awareness campaigns need to be carried out to eliminate stigma and stereotypes about people with disabilities in the world of work. More research is needed to continue to identify the barriers faced by people with disabilities and develop more effective solutions.